WDR62 overexpression is associated with a poor prognosis in patients with lung adenocarcinoma. Issue 8 (30th March 2017) - Shinmura, Kazuya; Kato, Hisami; Kawanishi, Yuichi; Igarashi, Hisaki; Inoue, Yusuke; Yoshimura, Katsuhiro; Nakamura, Satoki; Fujita, Hidehiko; Funai, Kazuhito; Tanahashi, Masayuki; Niwa, Hiroshi; Ogawa, Hiroshi; et al.
Abstract : Human WDR62, which is localized in the cytoplasm including the centrosome, is known to be responsible for primary microcephaly; however, the role of WDR62 abnormality in cancers remains largely unknown. In this study, we aimed to reveal the pathological role of WDR62 abnormality in lung adenocarcinoma (LAC). We first examined the WDR62 mRNA expression level of LAC ( n = 64) using a QRT‐PCR analysis and found that WDR62 mRNA transcripts were significantly overexpressed in LAC ( P = 0.0432, Wilcoxon matched pairs test). An immunohistochemical analysis for LAC ( n = 237) showed that WDR62 proteins were also significantly overexpressed in LAC ( P < 0.0001, Mann‐Whitney U test). A Kaplan‐Meier analysis demonstrated that patients with LAC who exhibit WDR62 overexpression have a short overall survival ( P = 0.0378, log‐rank test), and a multivariate analysis revealed that WDR62 overexpression was an independent predictor of a poor survival outcome among LAC patients (hazard ratio, 2.032; 95% confidence interval, 1.071‐3.777; P = 0.0305). Next, we examined the functional effect of WDR62 overexpression on the lung cancer cell line H1299. WDR62‐overexpressing lung cancer cells exhibited an increase in cell growth. Moreover, the concurrent overexpression of WDR62 and TPX2, a WDR62‐interacting protein that is also overexpressed in LAC, induced centrosome amplification in the lung cells. Finally, we disclosed that the concurrent overexpression of WDR62 and TPX2 is common in diverse human cancers, using data from the Cancer Genome Atlas. These results suggested that WDR62 overexpression is associated with a poor prognosis in patients with LAC and leads to an increase in the malignant potential of lung cells.